Nascimento de um filho :o significado para o pai - Carvalho, Jovanka Bittencourt Leite de (2005)
Qualitative study on the meaning of a child s birth to the father. Its general purpose was to comprehend the significance the man attaches to his child s birth and its specific objectives were to identify the man s feelings with regard to his child s birth as well as to verify his attitude toward a child s birth. The study was founded on the theoretical reference system about the man in the gravid-puerperal cycle and the humanization of the assistance. The data were obtained through semistructured interview performed with men accompanying their children s birth whose wives were in the immediate puerperium. This stage occurred in two maternity hospitals in Natal-RN, both of which adopt the principle of safe notherhood in the attendance of women in the process of parturition. The material apprehended from the statements was treated in conformity with the content analysis method in the mode of thematic analysis according to Bardin. Three thematic categories emerged from this process: the father s attitude toward his child s birth, the father s feelings in respect of his child s birth, and the informations received by the father in the course of his child s birth. The speech content was analyzed in accordance with the principles of symbolic interactionism according to Blumer. The results showed that the husbands interact with their respective wives and respond with attitudes of care, help, support, and encouragement within the principles of humanization intermingled with feelings of happiness, restlessness, and suffering leading them to appraise and exalt their consorts. Besides, we verified that the father s attitudes and feelings in the delivery room in the light of symbolic interactionism tend to be influenced by the interaction between him and the attending professionals